Georgia Solid Waste Sector Assessment Report - World Bank (World Bank, Washington, DC, 2021)
Since 2015, a year of the adoption of the Waste Management Code, Georgia has achieved significant progress towards an integrated solid waste management system. Regardless, there are several solid waste management challenges that the country struggles to overcome and is far from meeting the ambitious targets detailed in the National Solid Waste Management Strategy, which is harmonized with European Union standards. Some of the challenges include the need for improving waste collection coverage; reducing waste quantities in landfills; managing waste in an environmentally sound, safe manner; eliminating illegal dumping and littering through better waste collection, monitoring, and law enforcement; transforming municipal solid waste (MSW) management service delivery organizations from almost fully subsidized entities into truly autonomous, self-sufficient organizations with full cost-recovery; and introducing circular economy principles, including those for waste prevention, re-use, redesign, recycling and recovery. With a view to identify key solid waste sector gaps looking at the sector holistically and suggest short to longer-term interventions together with required investments, in mid-January 2021 the World Bank launched a solid waste sector study. The study was carried out by a team of local and international experts using combined methods of a desk review of existing literature and data, interviews with key decision-makers (e.g. representatives of the Ministry of Environmental Protection and Agriculture (MEPA), Solid Waste Management Company of Georgia (SWMCG) and cleaning /amenity services of local municipalities), questionnaire surveys of local municipalities, a gap analysis and, a spatial analysis via application of Geo-Information Systems (GIS). This paper seeks to assess high-level, solid waste management in Georgia to identify gaps in implementation of the National Waste Management Strategy (NWMS) and National Waste Management Action Plan (NWMAP) and to propose solutions linked to an operational roadmap and a program for short-, medium-, and long-term interventions for hard and soft investments.